Recent advances in polysaccharides derived from the Dendrobium nobile Lindl.: preparation strategies, structural characteristics, biological activity, and structure-activity relationships - Zhou, Xiao; Bi, Haizheng; Zhang, Zhaojiong; Wang, Xingyu; Zhang, Mengru; Wang, Meng (Frontiers in Pharmacology, 2025)
Dendrobium nobile Lindl. (D. nobile) has significant medicinal value. D. nobile is used in traditional Chinese medicine and is widely popular as a functional food and health supplement due to its nourishing properties and high safety. Among its key bioactive constituents, polysaccharides exhibit promising applications across medicine, personal care, food, and agriculture, owing to their anti-photoaging, improvement of complications of diabetes mellitus, ovarian protective, gastric protective, neuroprotective, anti-inflammatory and anti-viral effects. Despite these multifaceted benefits, research on D. nobile polysaccharides remains limited relative to more extensively studied components such as alkaloids and flavonoids. This review systematically summarizes current advances in extraction techniques, structural features, bioactivities, and structure–activity relationships of D. nobile polysaccharides, providing a theoretical framework for their future medical development and application.